The Effect of Logos in Marketing Communications on Consumer Behavior - Rizqi Muttaqin; Denny Saputera; Rizal Budi Santoso (International Journal of Economics (IJEC), 2023)
The purpose of this study is to research customers behavior on product representation by a company's logo and emblem (logo with text), with a particular emphasis on whether logos or emblems influence brand awareness from a consumer standpoint. This study's methodology is exploratory in nature, using a focuss group discussin approach as part of qualitative descriptive methods that includes a reference of the relevant literature related to branding. A focus group discussion is held in preparation for the two focus groups that will be held. The first focus group identified a logo with no brand name or logo text, while the second group identified the identical (original) logo with logo text or an emblem. This study's sample consists of students from the Bandung area, the majority of whom represent the target demographic., that the majority of whom represent the brand's target market segment. When the logo includes the brand text, the brand's awareness is best represented. The text's presentation of descriptive information about the brands was chosen by the consumer. As an example, the multi-national brand logo was used in this study. More trials with different brands are needed to generalize and corroborate the findings. Furthermore, the limitation of this study constraints, its only based on two small sample groups represented as potential consumer. The findings of this article imply that logos containing text influence consumers more perceptions of a brand's information and should thus be taken into account when altering a company's logo. Although there is a trend toward dressing-down logos in response to internationalization and digitization industry, it is beneficial to use brand logos that combine logo and emblem, rather than only pictorial logo marks, to communicate desired attributes of their brand personality.